2017
DOI: 10.3389/fpsyg.2017.00501
|View full text |Cite
|
Sign up to set email alerts
|

Review on Neural Correlates of Emotion Regulation and Music: Implications for Emotion Dysregulation

Abstract: Previous studies have examined the neural correlates of emotion regulation and the neural changes that are evoked by music exposure. However, the link between music and emotion regulation is poorly understood. The objectives of this review are to (1) synthesize what is known about the neural correlates of emotion regulation and music-evoked emotions, and (2) consider the possibility of therapeutic effects of music on emotion dysregulation. Music-evoked emotions can modulate activities in both cortical and subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 131 publications
(226 reference statements)
0
33
0
3
Order By: Relevance
“…The cingulum is also activated in both normal and pathologic anxiety 27,56 . Second, MD and RD values in the ILF has been found to be negatively correlated with anxiety scores, which is due to the abnormal functional connectivity of the fusiform and inferior temporal gyrus with the amygdala and insula (regions responsible for emotional processing [57][58][59][60][61][62] which is also seen in SAD patients 35 . Third, the FMa, which is located at the interface between crossing fibers from the splenium of the corpus callosum and ILF 63 , has been found to be associated with anxiety symptoms 64 .…”
Section: Discussionmentioning
confidence: 99%
“…The cingulum is also activated in both normal and pathologic anxiety 27,56 . Second, MD and RD values in the ILF has been found to be negatively correlated with anxiety scores, which is due to the abnormal functional connectivity of the fusiform and inferior temporal gyrus with the amygdala and insula (regions responsible for emotional processing [57][58][59][60][61][62] which is also seen in SAD patients 35 . Third, the FMa, which is located at the interface between crossing fibers from the splenium of the corpus callosum and ILF 63 , has been found to be associated with anxiety symptoms 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate a connection between singing as a means of self-expression, regulation of emotions, and health and well-being [5759]. Moreover, the availability of psychobiological methodology over the last decades such as the ambulatory assessment of humoral stress markers or functional imaging have confirmed that the experienced stress releasing effects of music have indeed a psychophysiological bases [60,61]. As Hou in his review elucidates, music-evoked emotions can modulate activities in both cortical and subcortical systems, and across cortical-subcortical networks [61].…”
Section: Singing Emotion Regulation and Well-beingmentioning
confidence: 99%
“…Moreover, the availability of psychobiological methodology over the last decades such as the ambulatory assessment of humoral stress markers or functional imaging have confirmed that the experienced stress releasing effects of music have indeed a psychophysiological bases [60,61]. As Hou in his review elucidates, music-evoked emotions can modulate activities in both cortical and subcortical systems, and across cortical-subcortical networks [61]. Exactly these networks, which extend from the anterior cingulate gyrus to the amygdala are integral and essential to the generation and regulation of emotions.…”
Section: Singing Emotion Regulation and Well-beingmentioning
confidence: 99%
“…It has been demonstrated that music is able to trigger behavioral changes, i.e., there is an underlying modification of brain function which can induce people to increase their exercise adherence and participation (Altenmüller and Schlaug, 2012). Music has also been demonstrated to be effective in reducing fatigue and its related symptoms (Jing and Xudong, 2008), in emotional regulation (Hou et al, 2017), in regulating affective arousal (Hutchinson et al, 2018) and in improving the efficacy of the motor system (Bigliassi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%